Yield loss of faba bean (Vicia faba L.) due to chocolate spot (Botrytis fabae Sard.) in Sinana, Southeastern Oromia - Kora, Dagne; Teshome, Ermias (Pure and Applied Science Advances, 2018)
Field experiment was conducted at Sinana Agricultural Research Center in the 2014 main cropping season with the objective to assess yield losses caused by chocolate spot (Botrytis fabae) of faba bean varieties. The highest number of days to physiological maturity was recorded on the variety Shalo (141.6 days) and lowest in the variety Mosisa (138.5 days). The maximum biomass on hectare basis (6.6t/ha) was obtained from plot sprayed at weekly interval. The maximum relative grain yield loss were recorded from the varieties of Mosisa and local, 47.8% and 46.7% on unsprayed plots, respectively. Losses in hundred seed weight greater on the variety local than others, this variety had maximum hundreds seed weight loss of 16% when it was protected against the diseases. The local variety shows the maximum biomass loss compared to other varieties under unsprayed plots. This variety has a biomass loss of 33% under unsprayed plots. The highest marginal benefit (32022.9 ETB/ha) was obtained from variety Mosisa sprayed at weekly intervals and highest (233.7 ETB) marginal rate of return was obtained also from this variety when treated at weekly intervals.